Reversible data hiding in encrypted images based on fine-grained embedding room reservation - Jinwei LI; Xiaoya ZHANG; Yuanzhi YAO; Nenghai YU (网络与信息安全学报)
Reversible data hiding in encrypted images has attracted considerable attention due to the privacy-preserving requirement for cloud data management.The good performance in this area can be achieved by using the existing framework of reserving room before encryption, where the image is partitioned to two independent slices consisting of blocks and then traditional reversible data hiding techniques are utilized to vacate room.In order to better exploit the spatial correlation of images, a fine-grained scalable embedding room reservation strategy in which blocks were rearranged to constitute the textured slice and the smooth slice was proposed.The block-size can be adjusted adaptively according to the texture of the images and the size of room to be vacated.The original locations of these blocks were efficiently represented as the to-be-embedded auxiliary information for image restoration.Because pixels in the smooth slice are easier to be predicted, the smooth slice can contain more pixel bits from the textured slice to reserve more room and fewer embedding distortions are induced with traditional reversible data hiding techniques.Extensive experiments demonstrate the merits of the proposed method in terms of embedding capacity and image quality.